II. Evaluation of apramycin sulphate in piglets in a novel oral formulation for the treatment of neonatal coliform diarrhoea: A dose titration study - ΚΥΡΙΑΚΗΣ Σ. Κ.; ΣΑΡΡΗΣ Κ.; ΤΣΑΛΤΑΣ Κ.; ΑΝΔΡΕΩΤΗΣ Ι. Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In a field trial conducted in Greece, 40 litters of piglets suffering from a natural infection of neonatal coliform diarrhoea were randomly assigned to treatments containing 0, 20, 30 and 40mg apramycin per 1. 1ml dose. Every piglet in each litter received orally, with the aid of a doser, a single dose of the same treatment once daily for 5 consecutive days. Over the two week trial period mortality was 9,9% in the untreated control, 2,2% in the 20mg group, 5,0% in the 30 mg group and 2,3% in the 40mg apramycin group. The reduction in overall mortality by the 20 mg and 40 mg treatments compared to untreated controls was significant (P<0,05). During the first week diarrhoea and sickness scores were significantly (P<0,05) lower in the 20mg apramycin treatment than the untreated control. In the second week all treatment groups had significantly lower scores than the untreated group, for the diarrhea score only. Overall, the average daily gain of the treated animals was improved by 12%, 15% and 8% over the untreated control group for the 20mg, 30mg and 40mg, apramycin treatments, respectively. Similarly, all three treatments improved the liveweight gain per pig started and had better mean day 14 piglet health scores and mean piglet viability scores, than the untreated controls. Escherichia coli were regularly cultured from rectal swabs taken both on day 0 an day 7 of the trial in all treatment groups and from the upper intestinal tract and visceral organs of piglets died during the trial. The study supports a dose range of 20-40mg apramycin orally per piglet, once daily for 5 days, for the treatment of neonatal diarrhoea.